Acoustics of the alignment of narrow focus prosody and lexical stress in native and nonnative English productions - Baek, Hyunah (Journal of the Acoustical Society of America, 2024)
This study examined the acoustic correlates of the alignment between lexical stress and narrow focus prosody in English and investigated how this alignment is learned by second language learners whose native language is prosodically distinct from English. A production experiment was conducted where native English speakers and Korean learners of English were asked to read aloud sentences with a narrow focus on trisyllabic words with various stress patterns (e.g., ánimal, Novémber, submaríne). In the native English productions, the stressed syllables were characterized by either a rising F0 contour (for word-initial stress) or increased periodic energy (for word-medial and -final stress). The Korean speakers (KSs) produced stressed syllables with a rising F0 contour regardless of stress position, differing from the native speakers, and they exhibited greater periodic energy for word-medial and -final stressed syllables, similar to the native speakers. In addition, the KSs with higher English proficiency showed more native-like patterns by exhibiting a post-focus F0 drop immediately after word-initial stressed syllables. These findings are discussed in the context of existing literature and potential factors contributing to the challenges observed in L2 prosody learning.
Keywords: Acoustic correlates; F0 contours; Initial stress; Native language; Periodic energy; Second language learners; Stress patterns; Adult; Female; Humans; Language; Male; Multilingualism; Phonetics; Reading; Sound Spectrography; Speech Acoustics; Speech Production Measurement; Voice Quality; Young Adult